Electron Microscopic Studies on Testis of Adult Ram - Gopi Krishna, B. (Indian Journal of Veterinary Anatomy, 2018)
The localization of the various enzymes in blood cells is of great importance in understanding body response to anyÂ kind of stress, disease or adaptability. Eosinophils showed weak reaction for acid and alkaline phosphatases but moderate reaction for cytochrome oxidase and peroxidase. Heterophils showed mild reaction for alkaline phosphatase, cytochromeÂ oxidase, peroxidase but negative for acid phosphatase activity. Basophils revealed mild reactivity for peroxidases. The lymphocytes and monocytes showed lack of activity for the enzymes.